Sub-acute toxicity of black seed (Nigella sativa) and honey mixture - Wong, Pei Lou; Suvik Assaw; Mohd Azrul Lokman; Nasrenim Suhaimin; Hayati Mohd Yusof (Penerbit Universiti Kebangsaan Malaysia, 2018)
Consumption of black seed (Nigella sativa) and honey mixture (BSH) has been reported to provide multiple health advantages. However, the toxicity effect of black seed and honey mixture (BSH) consumption has not been reported, although it has been consumed for centuries. Thus, this toxicity study was conducted, including determination of 50% lethal dose (LD50), changes in body and relative organ weights, differential leukocytes count, liver function test and histopathology analysis of liver and kidney. Thirty male Sprague Dawley rats (120-300 g) were used in the study and treated with varying dosages of BSH (100, 500, 1000 and 2000 mg/kg, respectively) for 14 days. Half of the rats from each group (n=3) were euthanized on day 14 for a sub-acute toxicity study to obtain relative organ weight, haematology, liver function test and histopathology analysis. Another half of animals from each group (n=3) were kept for another 14 days without any treatment for delayed toxicity study. No lethality was observed in all dosage groups, while the LD50 value was evaluated to be more than 2000 mg/kg. No significant alterations (p>0.05) were observed in animal body weight, differential leukocytes count and relative organ weight in all treatment groups as compared to control for both sub-acute and delayed toxicity studies. However, AST enzymes drop significantly at dosage 500 and 2000 mg/kg in recovery period, which suggested delayed hepatoprotective effect of the mixture. Histopathology analysis of the liver and kidney confirmed no abnormalities in cell morphology. This study clearly demonstrates that consumption of BSH is safe and do not provide any adverse or delayed toxicity effect.